Investigation of listeria spp in chicken meat consumed in erzurum - Emre Kaya; Mustafa Atasever (Eurasian Journal of Veterinary Sciences)
Aim: This study was conducted to determine the presence and prevalence of Listeria spp. in chicken meat in Erzurum province. Materials and Methods: In this study, 100 chicken thigh meat samples which were consumed in Erzurum were analyzed. In the isolation and identification of Listeria spp. species were used TS EN ISO 2017 method and Microbact 12 L Listeria Identification test Kit. Results: 64 (64%) Listeria spp were isolated in 64 (64%) out of 100 chicken meat samples, identification of those indicated 16 (25 %) isolates as L. monocytogenes, 26 (40.62 %) as L. innocua, 12 (18.75